Pengaruh Penyuluhan Kebencanaan terhadap Tingkat Pengetahuan Siswa SMP Sebelas April dalam Menghadapi Bencana Tanah Longsor - Nova; Haryeti, Popon; Prameswari, Ayu (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Landslides are one of the disasters that often occur in Indonesia. Landslide disasters cause a lot of material loss and casualties. South Sumedang is one of the sub-districts that experiences the most landslides in Sumedang Regency. Preparedness that can be done to reduce the impact of landslides is by conducting education. Objective: This research aims to determine the effect of disaster education on the level of knowledge of Sebelas April Middle School students in dealing with landslides. Methods: This research used Quasi-Experimental with a Pretest-Posttest Nonequivalent Control Group Design. The sample consisted of 112 students and data analysis used Wilcoxon. Results: The results of the research show a p-value of 0.001, which means there is a difference in the knowledge of Sebelas April Middle School students between before and after counseling. Discussion: It was concluded that counseling had a significant effect on increasing students' knowledge in dealing with landslide disasters.